Laras dan Rumpaka dalam Garap Karawitan Jaipongan Jugala - Ismet Ruchimat; R.M. Soedarsono -; Timbul Haryono; Tati Narawati (LP2M ISBI Bandung, 2013)
ABSTRACT This paper analyzes characteristic and musical identity of garap karawitan Jaipongan which is focused on the identity of laras and rumpaka. The identity of karawitan Jaipongan is a genre of today’s Sundanese karawitan which developes without any acculturation influence. Most verbal form of rumpaka on garap karawitan Jaipongan Jugala represents a dialogue or text that requires comprehension of the content. The characteristic of laras and rumpaka which are verbal and musical in garap karawitan Jaipongan show a multidimensional artistic expression. Keywords: characteristic, laras, rumpaka, Jaipongan, and jugala ABSTRAK Tulisan ini menguraikan ciri-ciri atau identitas musikal garap karawitan Jaipongan Ju- gala yang dititikberatkan pada identitas laras dan rumpaka. Identitas karawitan Jaipongan merupakan suatu genre karawitan Sunda kiwari yang berkembang tanpa pengaruh besar akulturasi. Bentuk verbal rumpaka pada garap karawitan Jaipongan Jugala sebagian besar merepresentasikan suatu pembicaraan atau teks yang menuntut pemahaman isi. Karakter- istik laras dan rumpaka yang bersifat verbal dan musikal dalam garap karawitan Jaipongan menunjukkan ekspresi artistik yang multidimensional. Kata kunci: karakteristik, laras, rumpaka, Jaipongan, dan jugala